Traditional Medicinal Knowledge in India and Malaysia - Madaleno, Isabel Maria (Pharmacognosy Communications)
Chronic diseases like diabetes, arthritis, rheumatism, asthma can be treated using ointments, infusions and concoctions. In Asia many endemic, native and exotic plant species have been consumed or applied for centuries, constituting a repository of knowledge reported in old manuscripts or transmitted by traditional healers, wild species collectors and urban gardeners. This paper presents information about 338 different vegetable species gathered in two Indian settlements – Goa and Kochi – in Malacca, Malaysia, and on the subject of their consumption both as food and as medicine. The aim of the Portuguese Tropical Institute is to provide a catalogue of medicinal flora existent in urban gardens that might improve the health of the less wealthy as well as those who have faith in natural treatments and alternative medicines.
Keywords: Biodiversity; Ethnobotany; Health; Nutraceuticals; Urban